2020
DOI: 10.1109/lra.2020.3013861
|View full text |Cite
|
Sign up to set email alerts
|

UFOMap: An Efficient Probabilistic 3D Mapping Framework That Embraces the Unknown

Abstract: 3D models are an essential part of many robotic applications. In applications where the environment is unknown a-priori, or where only a part of the environment is known, it is important that the 3D model can handle the unknown space efficiently. Path planning, exploration, and reconstruction all fall into this category. In this paper we present an extension to OctoMap which we call UFOMap. UFOMap uses an explicit representation of all three states in the map, i.e., unknown, free, and occupied. This gives, sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(39 citation statements)
references
References 30 publications
0
39
0
Order By: Relevance
“…Pruning makes the map more memory efficient and faster to search in compared to a naive implementation of an occupancy grid since it reduces the number of nodes without losing any information about the environment. Duberg and Jensfelt [2] build on the work of Wurm et al [1] and models unknown space explicitly which is suitable for exploration where unknown space often is accessed. Their implementation is also faster to manipulate than Octomap.…”
Section: Octree Occupancy Mapmentioning
confidence: 99%
See 2 more Smart Citations
“…Pruning makes the map more memory efficient and faster to search in compared to a naive implementation of an occupancy grid since it reduces the number of nodes without losing any information about the environment. Duberg and Jensfelt [2] build on the work of Wurm et al [1] and models unknown space explicitly which is suitable for exploration where unknown space often is accessed. Their implementation is also faster to manipulate than Octomap.…”
Section: Octree Occupancy Mapmentioning
confidence: 99%
“…The assumption that the environment is static when exploring but dynamic when not exploring is made as the proposed solution models the probability that a voxel changes its state between visits of a scene. The map used are based on an octree occupancy grid developed by Duberg and Jensfelt [2] as described in section 2.1.1 but contains further information on the dynamics of the environment based on the work of Saarinen, Andreasson, and Lilienthal [3].…”
Section: Dynamical Map Representationmentioning
confidence: 99%
See 1 more Smart Citation
“…In the literature, Octomap [18] and UfoMap [10] are two open-source approaches that can be used to implement a map from the point cloud data. In [10], it is shown that UfoMap is more advantageous to represent the unknown region, more memory efficient and achieves faster insertion times than Octomap. However, we implement our local map as the Octomap structure for two reasons.…”
Section: Local Mapmentioning
confidence: 99%
“…The nearby clutter value Π clut j is calculated for each trajectory j as in Eq. (10). Here, the first variable Ω tot j equals to the sum of all Priority and Support voxel weights β i .…”
Section: Nearby Cluttermentioning
confidence: 99%